Direct Effect of Two Naphthalene-Sulfonyl-Indole Compounds on Toxoplasma gondii Tachyzoite - Qasem Asgari; Hossein Keshavarz; Mostafa Rezaeian; Mohammad Hossein Motazedian; Saeedeh Shojaee; Mehdi Mohebali; Ramin Miri (Journal of Parasitology Research)
Past studies have stated that the parasitostatic effect of IFN-γ is most likely due to the starvation of Toxoplasma gondii for tryptophan in the host cell. The aim of this study was to evaluate the direct effect of two new Naphthalene-Sulfonyl-Indole compounds as competitive molecules for tryptophan on viability and infectivity of Toxoplasma tachyzoites. Tachyzoites of RH strain were incubated in various concentrations (25–800 μM) of 1-(naphthalene-2-sulfonyl)-2,3-dihydro-1H-indole and 1-[5-(2,3-dihydro-1H-indole-1-sulfonyl)naphthalene-1-sulfonyl]-2,3-dihydro-1H-indole for 1.5 hours. Then, they were stained by PI and analyzed by FACS. To evaluate the infectivity, 2×106 tachyzoites exposed to the concentrations mentioned above were intraperitoneally inoculated into five mice from each group. Also, naïve parasites and parasites exposed to DMSO (control) were inoculated in both groups of mice. The LD50 of 1-(naphthalene-2-sulfonyl)-2,3-dihydro-1H-indole was 62 μmol whilst the quantity of 1-[5-(2,3-dihydro-1H-indole-1-sulfonyl)naphthalene-1-sulfonyl]-2,3-dihydro-1H-indole was more than 800 μmol. The infectivity of tachyzoites exposed to both of the compounds preserved and killed mice. No statistical correlation was seen between longevity of mice groups and different doses of the compounds. If we consider a well-organized transporter mechanism for indole compounds in the parasite, thus the designation of an antagonist that has indole groups can assist with the production of new drugs.